2020
DOI: 10.1021/acsaelm.0c00635
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance, Transparent Solution-Processed Organic Field-Effect Transistor with Low-k Elastomeric Gate Dielectric and Liquid Crystalline Semiconductor: Promises and Challenges

Abstract: This is a repository copy of High performance, transparent solution-processed organic field effect transistor with low-k elastomeric gate dielectric and liquid crystalline semiconductor: Promises and Challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Spin‐coating, as the most widely used method for the deposition of thin film, could combine with other methods to fabricate organic semiconducting channels. [ 68,69 ] In order to make C8‐BTBT crystal more oriented, Yuan et al grew a highly aligned metastable structure from a blended solution of C8‐BTBT and polystyrene (PS) by adopting a novel OCSC method. [ 70 ] The resulting thin film could ascribe to passivation effect and increased solution viscosity due to the presence of PS during OCSC.…”
Section: Fabrication Techniques Of Btbt Derivative Thin Filmmentioning
confidence: 99%
“…Spin‐coating, as the most widely used method for the deposition of thin film, could combine with other methods to fabricate organic semiconducting channels. [ 68,69 ] In order to make C8‐BTBT crystal more oriented, Yuan et al grew a highly aligned metastable structure from a blended solution of C8‐BTBT and polystyrene (PS) by adopting a novel OCSC method. [ 70 ] The resulting thin film could ascribe to passivation effect and increased solution viscosity due to the presence of PS during OCSC.…”
Section: Fabrication Techniques Of Btbt Derivative Thin Filmmentioning
confidence: 99%
“…For example, Zheng et al reported a method to improve the efficiency of organic solar cells based on poly (3-hexylthiophene) and [6,6]-phenyl-C61-butyric acid methyl ester derivatives blends. A discotic liquid crystal [2,3,6,7,10,11]-hexabutoxytriphenylene (HAT-C4) was introduced at the interface between the active layer and a hole transporting layer, and they found that HAT-C4 molecules distribute in the active layer to form a more efficient pathway for carriers, resulting in a maximum 43% improvement in the PCE with the insertion of HAT-C4. Note that this method is applicable to three different hole transporting materials including poly(3,-4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT: PSS), MoO 3 and NiO.…”
Section: Nonvolatile Memory Applicationsmentioning
confidence: 99%
“…To be specific, liquid crystalline states are correlated to both orientational and positional order for molecular arrangements, and liquid crystals are extensively applied in electronic and optical devices. For example, calamitic liquid crystals have been extensively applied in broad electronic devices including flat panel displays, [ 4 ] thermometers, [ 5 ] field‐effect transistors, [ 6,7 ] and their corresponding discotic counterparts were developed as optical compensator films for displays and gas sensors. [ 8,9 ] With regard to the cholesteric liquid crystals, thanks to the intrinsic self‐organized helical structure, they are capable of fulfilling mirrorless band‐edge lasers and many other optical applications beyond displays by forming microspheres and microshells in immiscible fluids or gels.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor devices have attracted considerable attention in recent years. In particular, organic semiconductors are being used in devices including organic photovoltaics (OPVs) 1 3 , organic light-emitting diodes (OLEDs) 3 6 , and organic field-effect transistors 2 , 7 13 including for fabricating biosensors and radio frequency identification (RFID) tags. Organic semiconductor devices afford advantages such as a low-temperature fabrication process, low cost, and high flexibility.…”
Section: Introductionmentioning
confidence: 99%